Integrasi Keterampilan Abad 21 dalam Pengembangan Perangkat Pembelajaran Pada Konsep Community of Inquiry - Anjas Rusdiyanto Soleh; Zainal Arifin (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This research aim to identify integration of 21st century skills in the development of learning tools.. This research uses qualitative research by applying descriptive methods. The source data in this study is a learning device that has been developed in the PPL Program of FKIP UMS with the pattern of the Prospective Teacher Motivator Program based on the concept of CoI. The data is the form of parts in learning tools which are the integration of 21 st century competency skills which consist of 4Cs. Data collection techniques in this study are note-taking and documentation techniques. Data were analyzed using content analysis techniques. The results of this study indicate that the integration of 21st century skills in the development of learning tools in the CoI concept includes four overall aspects, namely critical thinking, creativity, communication, and collaboration or 4C, found in the Lesson Plan, Student Worksheet, and evaluation instrument. Its relevance to the CoI concept that critical thinking integrated in the cognitive presence aspect, creativity integrated in the social presence aspect, and communication and collaboration in the teaching presence aspect.